Polisi Wanita Indonesia dan Dinamika Sosial Tahun 1948-1961 - Kristiani, Sinta; Syukur, Abdul; Husmiati, Ratu (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2021)
This research aims to examine the process formation and development of the women police in the midst of the social dynamics that occurred in 1948-1961. Women police officers cannot be separated from the series of events that occurred in Indonesia post-independence. The method used in this research is the historical method which consists of five stages, namely topic selection, source collection, verification, interpretation, and writing. The existence of women police officers was motivated by the need for women to examine refugees, witnesses, or victims of crime after the Dutch Military Aggression I. The Sumatran police service conducted a selection of women police officers starting on September 1, 1948. Changes in security conditions also influenced the development of women's police education which was discontinued as a result of Dutch Military Aggression II. After women police struggled to deliver the opening of women police officers together with Bhayangkari, the reception of women police officers was reopened in 1961 and regulates in law No. 13/1961 of women police. In addition, the task of women police officers is expanded beyond just dealing with women and children’s issues.Penelitian ini bertujuan untuk mengkaji proses pembentukan serta perkembangan Polisi Wanita Indonesia di tengah dinamika sosial yang terjadi tahun 1948-1961. Pembentukan Polisi Wanita tidak lepas dari rangkaian peristiwa yang terjadi di Indonesia pasca kemerdekaan. Metode yang digunakan dalam penelitian ini adalah metode sejarah yang terdiri dari lima tahap yaitu pemilihan topik, pengumpulan sumber, verifikasi, interpretasi dan penulisan. Adanya Polisi Wanita dilatarbelakangi oleh kebutuhan wanita untuk memeriksa para pengungsi, saksi atau korban kejahatan pasca Agresi Militer Belanda I. Jawatan Kepolisian cabang Sumatera melakukan seleksi penerimaan Polisi Wanita dimulai pada 1 September 1948. Perubahan kondisi keamanan turut serta berpengaruh terhadap perkembangan pendidikan Polisi Wanita yang sempat dihentikan akibat Agresi Militer Belanda II. Setelah Polisi Wanita berjuang menyampaikan pembukaan Polisi Wanita bersama Bhayangkari, penerimaan Polisi Wanita dibuka kembali pada tahun 1961 dan diatur dalam Undang-Undang No.13 Tahun 1961 tentang Polisi Wanita. Selain itu, tugas Polisi Wanita diperluas tidak hanya berhubungan dengan permasalahan wanita dan anak.